Word Meaning in Lexical Semantics: A Literature Review of Nouns, Adjectives, Verbs, and Figurative Language - Citra Umi Kultsum Salsabila; Defarra Al-Zahwa; Aidil Syahputra (Lembaga Pengembangan Kinerja Dosen, 2026)
Word meaning is one of the central topics in linguistic theory because it connects language structure, human cognition, and cultural experience. This literature review examines word meaning from the perspective of lexical semantics, focusing on how nouns, adjectives, and verbs construct meaning differently and how figurative mechanisms such as metaphor, metonymy, and idioms extend literal meaning. Using a library research approach, the study synthesizes classical semantic theories proposed by Bloomfield, Lyons, and Jespersen with cognitive semantic frameworks developed by Lakoff, Fillmore, Talmy, Evans and Green, as well as recent empirical studies published between 2019 and 2025. The review shows that noun meaning is shaped by denotation, prototype structure, and frame knowledge, while adjective meaning is inherently context-dependent and organized along semantic scales. Verb meaning is explained through aspectual classification, event structure, and force dynamics, providing a more comprehensive understanding of lexical representation. The analysis further demonstrates that figurative language is not merely a stylistic feature but reflects systematic conceptual mappings that organize human thought, as explained in Conceptual Metaphor Theory and cognitive accounts of metonymy. The findings indicate a significant shift from traditional reference-based semantics toward cognitive semantics, highlighting that these approaches complement rather than replace one another. The review also emphasizes pedagogical implications for English language teaching by suggesting that explicit instruction in conceptual metaphor, frame knowledge, and idiomatic expressions can improve learners' lexical and figurative competence. Overall, word meaning is best understood as a dynamic, usage-based, and culturally embedded phenomenon shaped by linguistic structure, cognitive processes, and communicative context.